Business Relationships Development in SEA - Paing, Mei Lian (My University, 2014)
In research one may find many thoughts about steps and strategies with regard to initiate successful business relationships in a multicultural context. However, earlier business relationship research has less focus on the Southeast Asia (SEA) region, especially when it comes to studies focussing on the initial stages of business relationships. Hence, the purpose of this Master’s thesis is to study the nature of business relationships and the initiation of business relationships in SEA. In order to cover the research topic appropriately, the model of attraction, interaction, communication, and trust and commitment have been applied. The abductive approach is applied to conduct this study. Data collection is based on semi-structured in-depth interviews with four interviewees from Finnish manufacturing companies in a business to business environment, three of the interviewees are Finns, and one is from Thailand. The result of this thesis is to contribute as a supportive guideline for companies planning to newly enter into the SEA market. The result of this Master’s thesis showed that Finnish companies used local partners to enter into these unfamiliar markets. Local partners and foreign companies are attracted to each other due to the resources needed. Local partners exchanged local market knowledge with technical and financial supports from foreign partners. In SEA, personal relationships are important and impact the business to a certain extent in the local business environment; however foreign counterparts often prefer to keep distance from local partners. Moreover, trust and commitment are based on results and actions which could create significant good result to the business.
Keywords: fi=Master's Degree Programme in International Business|